2017
DOI: 10.5614/j.math.fund.sci.2017.49.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Estimation of Engineering Bedrock Depths from Microtremor Array Measurements in Solo, Central Java, Indonesia

Abstract: In the last decade the city of Solo, located in Central Java, Indonesia, has grown significantly and become a major city. Many industries and hotels have been built in the city and its surroundings. This study aimed to determine the engineering bedrock depths in Solo, an important parameter in seismic hazard analysis. The microtremor array method was used to obtain 1D S-wave velocity profiles and construct layer depth maps. The spatial autocorrelation (SPAC) method was used to calculate the dispersion curves, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This method was developed by Figure 1. Geological map of Surakarta city, the solid yellow dot is geoelectric survey locations (modified from Koesuma et al, 2017) Aller et al in 1987 for the US Environmental Protection Agency (Putranto et al, 2016). Assessment of groundwater vulnerability uses seven hydrogeological parameters, including depth of water table (D), net recharge (R), aquifer media (A), soil media (S), topography (T), impact of vadose zone (I), and hydraulic conductivity (C) (Wachniew et al, 2016).…”
Section: Drastic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was developed by Figure 1. Geological map of Surakarta city, the solid yellow dot is geoelectric survey locations (modified from Koesuma et al, 2017) Aller et al in 1987 for the US Environmental Protection Agency (Putranto et al, 2016). Assessment of groundwater vulnerability uses seven hydrogeological parameters, including depth of water table (D), net recharge (R), aquifer media (A), soil media (S), topography (T), impact of vadose zone (I), and hydraulic conductivity (C) (Wachniew et al, 2016).…”
Section: Drastic Methodsmentioning
confidence: 99%
“…The city is covered by quaternary sediment, which is mostly alluvium. The stratigraphic sequence follows the metamorphic rock consisting of schist, marble, altered volcanic, and sedimentary rock, the oldest formation in this area (Koesuma et al, 2017).…”
Section: Description Of Research Areamentioning
confidence: 96%
“…The information of the wave propagation from bedrock to soil surface has been studied using ground response analysis and indicates that the soil layer of Surakarta tends to amplify the ground motion of the earthquake wave. The geophysics study using microtremor analysis was later reported that the location of bed rock surface of Surakarta is at a depth variation of 145 m to 185 m [19]. The result of the geophysics studies also provided the information of shear wave velocity at a depth of 30 m from the surface and the variation of seismic site class map of Surakarta [20].…”
Section: Figure 1 the Location Of Surakartamentioning
confidence: 97%
“…The ambient vibration data collected using the single station and array microtremor results were analyzed using the horizontal to vertical spectrum ratio (HVSR) and inversion methods [4][5][6][7]. The purpose of HVSR analysis is to predict the bedrock elevation at the microtremor test position.…”
Section: Microtremor Investigationmentioning
confidence: 99%